Improvement of reduced activation 9%Cr steels by ausforming. (January 2016) - Hoffmann, J.; Rieth, M.; Commin, L.; Fernández, P.; Roldán, M.
Highlights: Improvement of conventional 9%Cr RAFM steels by thermo-mechanical treatments has been demonstrated. Superior strength and prolonged creep lifetime has been found for EUROFER steel after TMT (e.g. 50 MPa in tensile strength at high temperatures). A nano-scale precipitation of strengthening secondary phases was found inside the materials. Abstract: For improved performance of the components in a fusion reactor, an increased application temperature for structural materials such as 9%Cr reduced activation steels is crucial. The improvement of the current generation of 9%Cr steels (i.e. EUROFER) is one of the aims of the current EUROfusion programme for advanced steels. The goal of this work is to determine the most effective thermo-mechanical treatment of reduced activation ferritic martensitic steels with respect to high-temperature strength. Compatibility of these treatments with industrial production processes is essential. In the present study, two different batches of EUROFER-2 were prepared with a thermo-mechanical treatment. The materials were solution annealed at 1250 °C and then slowly cooled to the rolling temperature, which was varied between 600 and 900 °C. Hot-rolling was performed in the austenite regime with a subsequent rapid cooling to form the ferritic-martensitic structure. The characterization of the materials was done in as-rolled state and after a subsequent tempering at 750 °C. The materials characterization was performed by tensile and Charpy impact tests using miniaturized specimens. The microstructure was characterized by scanning electron microscopy (SEM) backscatter images and electron backscatter diffraction (EBSD) maps. All the results were compared to those of conventionally processed EUROFER-2 alloys. The first results show a gain in tensile strength of approximately 50 MPa at temperatures above 600 °C compared to conventionally treated EUROFER alloys. Microstructural investigations reveal a fine and homogeneous distribution of the martensitic laths, while the prior austenite grains are about one order of magnitude larger. This can be explained by the exceptionally high austenitization temperature compared to the as-received state.